2011
DOI: 10.1111/j.1365-2621.2011.02775.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of total phenols, flavonoids, saponins and antioxidant activity in yellow soy beans and mung beans

Abstract: Total phenol, flavonoid and saponin content of soy bean and mung bean were systemically compared in order to evaluate their contribution to overall antioxidant activity. Mung bean extract possessed significantly higher total phenol (2.03 GAE g )1 vs. 1.13 GAE g )1 ) and flavonoid contents (1.49 GAE g )1 vs. 0.41 CAE g )1 ) than soy bean extract, while the saponin content of the soy beans was 4.5 times greater than that of the mung beans. In several antioxidant assays including DPPH and ABTS radical scavenging,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 31 publications
6
58
0
6
Order By: Relevance
“…The mean values obtained (5.226 mg Trolox g −1 DM by DPPH and 5.026 mg Trolox g −1 DM by ABTS) revealed considerable antioxidant capacity. These values are consistent with those obtained by Barbosa et al and Lee et al in defatted soybean seeds and flour, respectively. However, it is difficult to compare our results to those of other reports because of multiple factors that can affect the antioxidant activity such as phenolic content and its profile, different phenolic extraction conditions and analytical methods used.…”
Section: Resultssupporting
confidence: 93%
“…The mean values obtained (5.226 mg Trolox g −1 DM by DPPH and 5.026 mg Trolox g −1 DM by ABTS) revealed considerable antioxidant capacity. These values are consistent with those obtained by Barbosa et al and Lee et al in defatted soybean seeds and flour, respectively. However, it is difficult to compare our results to those of other reports because of multiple factors that can affect the antioxidant activity such as phenolic content and its profile, different phenolic extraction conditions and analytical methods used.…”
Section: Resultssupporting
confidence: 93%
“…Our study found that the TPC in the papaya leaf extract had a stronger correlation to the antioxidant, free radical scavenging and ion‐reducing capacity than saponins content (Table ). These findings were supported by previous studies (Javanmardi et al ., ; Lee et al ., ; Li et al ., ; Molan et al ., ) as phenolic compounds were demonstrated to possess high antioxidant capacity due to the presence of redox active groups in their structures (Pisoschi & Negulescu, ); whereas, saponins are composed of sapogenin, sugars and organic acids (Li et al ., ). Although possessing low antioxidant capacity, saponins have been found to demonstrate anticancer properties (Shi et al ., ; Li et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The potential health benefits of flavonoids as highly effective and less toxic natural antioxidants than synthetic antioxidants (e.g. BHA, BHT and so on) have made them very important additives in the manufacture of foods, industrial products and biopharmaceuticals (Chen et al, 2011;Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%